Parieto-Occipital Interhemispheric Transfalcine, Trans-Bitentorial Approach for Radical Resection of Falcotentorial Meningiomas - Okada, Tomu; Miyahara, Kousuke; Tanino, Shin; Suzuki, Kouji; Watanabe, Nobuyuki; Tanaka, Yuusuke; Hataoka, Syunsuke; Uriu, Yasuhiro; Ichikawa, Teruo; Fujitsu, Kazuhiko; Niino, Hitoshi; Yagishita, Saburou (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective Falcotentorial meningioma occurs close to the falcotentorial edges and the confluence of the vein of Galen. The posterosuperior approach conventionally used to reach this site does not allow direct visualization of the tumor matrix, making detachment difficult. Meningiomas at this location are therefore among those that are not well amenable to radical resection. We devised an alternative anterolateral approach that, when used in addition to the posterosuperior approach, provides an operating field which allows to overview large, bilaterally extending tumors. We report this parieto-occipital interhemispheric transfalcine, trans-bitentorial approach, together with associated procedural modifications.Methods We used the approach in four patients with falcotentorial meningioma between February 2008 and July 2017. We began by extending a parieto-occipital craniotomy slightly beyond the midline, to pass across the most caudal bridging vein on the rostral side. We then created a fan-shaped fenestration as large as possible in the falx, between the superior sagittal sinus and the inferior sagittal and straight sinuses (window 1). We further performed wedge-shaped resections of both tentorial edges to the left and right of window 1 (windows 2 and 3). Tumor debulking was then carried out via these three windows (the triple-window method). Finally, we detached the tumor in the area of the falcotentorial edges and the confluence of the vein of Galen. To obtain a superorostral operating field as wide as possible from laterally, thereby exposing the potential blind spots, the operating surgeon used both hands while retracting the precuneus, and the assistant surgeon used both hands to turn over the falcotentorial edges (twosome four-hand retractorless microsurgery).Results The wide operating field provided by this parieto-occipital interhemispheric transfalcine, trans-bitentorial approach and twosome four-hand retractorless microsurgery provides a direct view of delicate structures at the falcotentorial edges and the confluence of the vein of Galen, a site that is most likely to be a blind spot in conventional approaches. Retraction of the precuneus on the nondominant side enabled radical resection with no neurologic deficit in any of the patients.Conclusions The parieto-occipital interhemispheric transfalcine, trans-bitentorial approach with the triple-window method opens an anterolateral operating field in addition to a posterosuperior operating field in large tumors located in the falcotentorial and pineal region, extending anteroposteriorly and bilaterally. The twosome four-hand retractorless technique via this approach enables visualization of the tumor matrix at sites, which are barely visible with the conventional approach. Thus, the tumor can be removed more radically and safely.
Keywords: falcotentorial meningioma; parieto-occipital interhemispheric transfalcine; trans-bitentorial approach; precuneus; triple-window method; twosome four-hand retractorless microsurgery